Konstruksi Teknologi Aplikasi sebagai Pengurangan Ketidakpastian dalam Komunikasi Antarpribadi : Fenomena Grindr - Putra, Fembiarta Binar (Faculty of Communications Science, Dr. Soetomo University, 2020)
As a minority with a closed tendency, homosexuals need the media to communicate with fellow community member. When they interact with each other, various kinds of uncertainties will be found, such as identity, personal status, background, and goals. This media is needed as part of reducing uncertainty with others. Through the Grindr application, a homosexual can get to know fellow homosexuals and can communicate intensely in interpersonal communications terms. This study aimed to find out how homosexuals in the Jakarta area who use Grindr as a medium to reduce uncertainty in relationships. The method of this research was the constructivist paradigm with a qualitative approach to explain the phenomenon comprehensively through interactions (in-depth interviews). The results of the research were that the respondents using Grindr in order to find friends or partners from the same community. The next step was to use other media for better ascertain in terms of finding friends or for pleasure. The conclusion is Grindr usage among homosexuals as part of reducing uncertainty in relationships, especially when they first building communication.